Understanding positional cues in salamander limb regeneration: implications for optimizing cell-based regenerative therapies - Catherine D. McCusker; David M. Gardiner (The Company of Biologists, 2014)
Regenerative medicine has reached the point where we are performing clinical trials with stem-cell-derived cell populations in an effort to treat numerous human pathologies. However, many of these efforts have been challenged by the inability of the engrafted populations to properly integrate into the host environment to make a functional biological unit. It is apparent that we must understand the basic biology of tissue integration in order to apply these principles to the development of regenerative therapies in humans. Studying tissue integration in model organisms, where the process of integration between the newly regenerated tissues and the 'old' existing structures can be observed and manipulated, can provide valuable insights. Embryonic and adult cells have a memory of their original position, and this positional information can modify surrounding tissues and drive the formation of new structures. In this Review, we discuss the positional interactions that control the ability of grafted cells to integrate into existing tissues during the process of salamander limb regeneration, and discuss how these insights could explain the integration defects observed in current cell-based regenerative therapies. Additionally, we describe potential molecular tools that can be used to manipulate the positional information in grafted cell populations, and to promote the communication of positional cues in the host environment to facilitate the integration of engrafted cells. Lastly, we explain how studying positional information in current cell-based therapies and in regenerating limbs could provide key insights to improve the integration of cell-based regenerative therapies in the future.